Publications in the Pedagogical Press as an Information Source about the Specifics of the Girls’ and Boys’ Schools Functioning in 1943 –1954 - Zhanna Stelmashuk (Pedagogical Discourse, 2013)
The article is devoted to the analysis of the pedagogical periodical press as a historical source of information about the topical problems of national school. The information potential of pedagogical press for the formation of the objective opinion of the researchers on a separate education at schools in the period of 1943-1954 is disclosed. Having used materials of the leading pedagogical journals («Soviet pedagogy», «Soviet school», «Public education» and «Primary school») and critical and comparative analysis of school content, the specifics of the girls’ and boys’ schools functioning in the period of 1943–1954 are shown. The author revealed the major trend of the publications and analyzed the most relevant materials on the problem. It is revealed that there were few publications which highlighted the life of the girls’ and boys’ schools. Most of them were an attempt to summarize the experience of an individual teacher or school, to cover particular aspects in the educational work organization. Attention is focused on publications of three authors (K.Lvov, O.Rayevsky and M.Тymofyeyev), where the most important views of the separate education introduction, peculiarities of functioning of the girls’ and boys’ schools in the analyzed period are considered. The ways of further development of the problem are defined.